Формування системи управління ризиками підприємства - Кукіна, Наталя Володимирівна; Оглобліна, Вікторія Олександрівна; Ткаченко, Єлизавета Юріївна; Kukina, Natalia; Ogloblina, Viktoriia; Tkachenko, Yelyzaveta (Запоріжжя : Видавничий дім «Гельветика», 2024)
UA: Досліджено сучасні підходи до визначення сутності ризику. Розглянуто підходи до формування системи управління ризиками підприємства. Проаналізовано зміст процесу управління ризиками на підприємстві. Запропоновано структуру та послідовність етапів формування системи управління ризиками на підприємстві. /// EN: The economic activity of an enterprise is accompanied by the action of numerous factors of the external and internal environment, which lead to the instability of its functioning. Therefore, the problems of managing various risks become relevant. Risk management at enterprises is provided by a system of regulation of economic, financial and other relations that arise under conditions of uncertainty. The process of forming a risk management system at an enterprise requires special attention. The purpose of the article. Research into the features of the formation of an enterprise risk management system. Specification of the content of the main stages of its formation. Research results. In modern economic conditions, in order to ensure stable work, the enterprise needs to take measures to reduce the level of economic risk. The development of directions for risk reduction requires the identification of relevant factors that generate it and an assessment of their significance. Enterprise risk management is aimed not only at identifying any risks, but also at managing the enterprise’s capabilities. The formation of an effective enterprise risk management system is proposed to be divided into the following stages: identification of risks; study of potential consequences of risks; risk priority assessment; formation of a risk prevention plan and elimination of their negative impact on the enterprise, control of the enterprise’s risk level. The detailing of the content of each stage and the development of a clear algorithm of the actions of the executors will allow to increase the effectiveness of the risk management system and ensure the timely response of the enterprise to external and internal threats.
Formation of an enterprise risk management system
Keywords: ризик; ідентифікація; оцінка; система управління; невизначеність; наслідки; risk; identification; assessment; management system; uncertainty; consequences